Infectious bronchitis virus: evolution and vaccination. Issue 1 (March 2016) - UMAR, S.; SHAH, M.A.A.; MUNIR, M.T.; AHSAN, U.; KABOUDI, K.
Abstract : The emergence and evolution of viral pathogens cause a major problem in the poultry industry. Mutation and recombination processes are involved in the genetic and phenotypic variations of infectious bronchitis virus (IBV) in chickens, leading to the emergence of new variant strains, and give rise to virus population diversity to be modelled by the host, particularly by the immune system. The consequence is the continuous emergence of new variants with regard to pathotypes, serotypes, and protectotypes. The viral genes encoding the spike, replicase and nucleocapsid proteins can be considered the main genomic regions, which indicate the evolution processes of IBV. Despite the use of vaccination, new IBV variants are evolving and circulating in the field and should be considered as initial candidates for vaccine development. The new generation vaccines developed against locally prevailing IBV strains may be more helpful and avoid the reversion of virulence in live vaccine viruses. Understanding the mechanisms underlying the evolution of IBV has basic relevance and, without doubt, is essential to appropriately control and prevention of the disease.